Linking industry concentration to proprietary costs and disclosure: Challenges and opportunities - Lang, Mark; Sul, Edward (Journal of Accounting and Economics, 2014)
Despite a substantial literature linking industry concentration, proprietary costs and disclosure, existing evidence is mixed. We discuss three challenges to the literature: lack of strong theoretical predictions, difficulty in measuring relevant aspects of industry concentration and difficulty in identifying disclosures that are likely to carry significant proprietary costs. We link each of the issues to the findings in Ali et al. (2014) and identify potential opportunities for future research.